"Cyberdating Q_A": An instrument to assess the quality of adolescent dating relationships in social networks. (July 2015) - Sánchez, Virginia; Muñoz-Fernández, Noelia; Ortega-Ruíz, Rosario
Highlights: Online quality of adolescents' dating relationships is explained by six dimensions. Online intimacy is very high among adolescents' dating couples. Boys are more involved in cyberdating practices than girls. Girls practice more emotional communication strategies than boys. Online intrusive behavior, jealousy, and control are not influenced by age. Abstract: The studies about the impact of new technologies and social networks on adolescent dating relationships are still considered emerging, especially in Spain. This study analysed the quality of cyberdating among adolescents by means of a mixed study. In a first study two focus groups were developed with the aim of exploring the positive and negative aspects of Internet and social networks for dating relationships. The results of this study were the base for developing a scale of the quality of cyberdating: The cyberdating Q _ A . The instrument was administered to 626 adolescents (average age 15.13; SD = 1.34; 51.4% males) and a cross-validation procedure was performed using exploratory and confirmatory factor analysis. Results confirmed a structure of six factors, namely online intimacy, emotional communication strategies, cyberdating practices, online control, online jealousy, and online intrusive behavior. Descriptive analysis showed that these scales were very frequent among adolescents, with boys scoring higher in intrusive behavior and cyberdating practices than girls. These results underlined the relevance of online activity in adolescent quality of dating relationships, so future research would benefit from considering an analysis of both overall and specific relationship quality measures in online settings by means of this new measure of cyberdating.